Can AnnAt1 of Arabidopsis thaliana contribute to Pb phytoremediation? - Phang, Ing Chia; Clark, Gregory B.; Taylor, H. Harry; Garrill, Ashley; Leung, David W. M. (2010)
Because of increasing anthropogenic outputs, lead (Pb) has gained attention as a potent environmental health hazard. Pb, a non-essential element, is persistent and cannot be degraded from the environment. This heavy metal contaminant is likely to enter human’s food chain, where it poses a hazard to public health. Phytoremediation has emerged as a potential remediation tool to remove heavy metal pollutants from the environment. The concept of plant-based environmental remediation is technically and economically attractive, compared to the conventional remediation methods. Although the response of different plants to different stressors varies, there are common stress-related genes that are involved in the detoxification of reactive oxygen species. This experiment was undertaken to further understand the molecular mechanisms plants employ to deal with Pb stress, focusing on the possible role of annexin 1 (AnnAt1) in Pb tolerance. Annexins are reported to be related to heat shock proteins, which are the most extensively characterized stress-response genes. Additionally, annexins have emerged as a key player in abiotic stresses, and are likely to play a role in Pb exposure. Using a quantitative real-time RT-PCR, the present study detected up-regulation of AnnAt1 in seedlings exposed to 100 μM Pb(NO3)2, by 2.12-fold, in comparison to the control plants. The relative contribution of AnnAt1 in defence against Pb stress will be discussed.